2013
DOI: 10.1080/17523281.2012.660981
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and comorbid substance use: association patterns in outpatient addictions treatment

Abstract: Depression and anxiety disorders commonly coexist with drug and alcohol use. Several general population surveys suggest non-linear associations between alcohol and depression symptoms. It is unclear whether such association patterns occur in clinical samples and in the context of poly-substance use. The aim of the study was to investigate the association patterns between substance use and common mental disorder (CMD) severity. Patients accessing a UK outpatient addictions service were recruited sequentially vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
1
11
0
1
Order By: Relevance
“…This study presents a detailed examination of symptom-level associations between common mental disorders (CMD), substance use and severity of dependence. To our knowledge, such analyses are rare [ 26 ], and offer novel information to validate theories about comorbidity and psychopathological processes. Consistent with the wider literature cited above, we found significant and moderate correlations between psychopathology and severity of dependence in a clinical sample of drug and alcohol users, although these were distinct and separate dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study presents a detailed examination of symptom-level associations between common mental disorders (CMD), substance use and severity of dependence. To our knowledge, such analyses are rare [ 26 ], and offer novel information to validate theories about comorbidity and psychopathological processes. Consistent with the wider literature cited above, we found significant and moderate correlations between psychopathology and severity of dependence in a clinical sample of drug and alcohol users, although these were distinct and separate dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most studies in this area examine associations at the level of syndromes or disorders, which could possibly mask specific symptom-level relationships and could also introduce artificial relationships because of double counting of symptoms [ 25 ]. For instance, in a recent study, severity of dependence has been found to correlate with several symptoms of depression and anxiety, whereas only few CMD symptoms were correlated with level of substance use and abstainers were just as likely to have a CMD diagnosis compared to users [ 26 ]. Symptom-level associations such as these have rarely been examined, and until such studies proliferate the debate about causal links will probably continue unabated.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in the USA have also found this frequent co‐occurrence (Kessler et al , 1996; Regier et al , 1990). In clinical populations, the reported prevalence of mood and anxiety disorders among people with SUD is much higher with UK studies showing frequencies of 70 per cent and above (Delgadillo et al , 2012; Weaver et al , 2003). However, the high prevalence of these mental disorders among people with SUD has been a subject of debate due to problems inherent in distinguishing independent mental disorders from substance‐induced mental disorders and the resulting implications on treatment strategies (Schuckit, 2006; O’Brien and Charney, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…For example, in a multi-national general population survey, approximately 26 per cent of alcohol-dependent and 35 per cent of drug-dependent cases were diagnosed with comorbid affective/mood disorders (Merikangas et al, 1998). The prevalence of mild through to severe depression cases in clinical samples of substance users is thought to be as high as 40-49 per cent (Delgadillo et al, 2013;Weaver et al, 2003).…”
Section: Introductionmentioning
confidence: 99%